Research on Bearing Capacity Characteristics of Cave Piles - Lixin Ou; Yufeng Huang; Xu Chen; Yang Xue; Qingfu Li; Biao Guo (Buildings)
To investigate the load-bearing characteristics of a pile foundation with multiple piles passing through karst caves and the extent of the caves’ influence, this study takes the Qihe Bridge, a key project of the second section of the Anhe Expressway, as a case study. Field tests on the bearing capacity of the pile foundation, passing through underlying karst caves, were conducted. Piles passing through the caves were selected as test piles, and a finite element analysis of the Qihe Bridge pile foundation structure was performed using Midas GTS NX 2022 software. After verifying the accuracy of the software’s calculation results, this study further explored the distribution patterns of factors such as axial force, side friction resistance, settlement, and relative displacement between the pile and soil with respect to the position of the pile. Special attention was given to monitoring locations at the interface between rock and soil layers, as well as within the depth range of the karst caves. The horizontal axial force on the piles was found to increase with the depth of the caves. By analyzing the distribution patterns of axial force, side friction resistance, settlement, and pile–soil relative displacement, the study clarifies the mechanism by which karst caves affect the load-bearing behavior of pile foundations.